Heterogeneity in College Student’s Technology-Facilitated Intimate Partner Violence Perpetration Occurring Post-Breakup: A Latent Profile Analysis - McMillan, Iris F. (Journal of interpersonal violence, 2023)
Technology-facilitated intimate partner violence (T-IPV), including social media surveillance (SMS) and cyber dating abuse (CDA), are increasingly common post-breakup experiences among college students. Although a large body of research has focused on identifying risk factors for both types of T-IPV, perpetrators of T-IPV may differ in their pattern of risk factors. Using the I3 model as a guiding framework, the current study sought to identify typologies of college students engaging in post-breakup SMS and CDA. Specifically, 710 college students’ responses on self-report measures were examined for similarities in known risk factors, namely attachment anxiety, impulse control difficulties, lack of emotion regulation strategies, intolerance of uncertainty, distress tolerance, and problematic alcohol use. Three distinct perpetrator profiles emerged with attachment anxiety, alcohol use, and intolerance of uncertainty presenting as distinguishing features. Problematic alcohol use was evident in the moderate and high levels of SMS and CDA perpetration profiles. Contrary to what was expected, there appeared to be little variability in emotional regulation and impulse control abilities across the three profiles such that individuals belonging to low and high perpetration profiles did not differ in the degree to which they were able to control their impulses or access emotion regulation strategies. Results highlight the potential importance of tailoring interventions, while reducing transdiagnostic risk factors, to account for the heterogeneity in risk factors among T-IPV perpetrators.